SPH modelling of a cavitation bubble collapse near an elasto-visco-plastic material. (April 2019) - Joshi, Shrey; Franc, Jean Pierre; Ghigliotti, Giovanni; Fivel, Marc
Abstract: A Smoothed Particle Hydrodynamics axisymmetric solver was developed in order to simulate the collapse of a single cavitation bubble close to an elastic-plastic material and study plasticity formation and hence material erosion. Findings indicate the relative importance of the material deformation due to the impact of the micro-jet and the shock wave that develop during collapse. A shock-wave dominated impact has a much higher material erosion ability compared to a micro-jet impact. Strain rate is found to have a significant effect on plastic deformation, with an overestimation of the plastic deformation up to 60% if strain rate effects are neglected in the case of stainless steel A2205. We also demonstrate that, although the impact pressure is maximum just below the collapsing bubble, maximum plastic strain occurs at a radial offset from the symmetry axis. This is the result of inertial effects that have an impact on both the magnitude and the position of the plastic domain in the material. A new non-dimensional parameter called effective pressure is introduced that can predict plastic strain location accurately for higher stand-off ratios. Alternatively, a characteristic time analysis also shows that it can be used for prediction of plastic strain zone in the solid for detached cavities.